Sostenibilidad y competitividad internacional de exportadores de camarón, en la provincia de El Oro - Coronel Rodriguez, Lady Veronica (Machala : Universidad Técnica de Machala, 2025)
This essay analyzes the relationship between certified sustainability and the international competitiveness of shrimp exporters in the province of El Oro, Ecuador. In a global context where certifications such as ASC, BAP, and Global GAP are key requirements for accessing premium markets, it is evident that certified companies achieve better prices, greater destination diversification, and greater attraction of foreign investment. Using a documentary and qualitative approach, it reviews academic studies and institutional reports that demonstrate that certification improves business reputation and productive efficiency. However, the paper also identifies significant barriers to the adoption of certifications, especially among small and medium-sized enterprises. These include high costs, lack of technical knowledge, limited institutional support, and a lack of tax incentives. These limitations generate inequality within the shrimp sector and hinder the transition to sustainable practices. The study concludes that certifications do strengthen international competitiveness, but require prerequisites that are not yet guaranteed for all stakeholders. It is recommended to implement supportive public policies, foster business alliances, and develop commercial strategies that capitalize on the benefits of sustainability.
"El ensayo analiza la relación entre la sostenibilidad certificada y la competitividad internacional de los exportadores de camarón en la provincia de El Oro, Ecuador. En un contexto global donde las certificaciones como ASC, BAP y Global G.A.P. son requisitos clave para acceder a mercados premium, se evidencia que las empresas certificadas logran mejores precios, mayor diversificación de destinos y mayor atracción de inversión extranjera. A través de un enfoque documental y cualitativo, se revisan estudios académicos e informes institucionales que demuestran que la certificación mejora la reputación comercial y la eficiencia productiva. Sin embargo, el trabajo también identifica barreras significativas para la adopción de certificaciones, especialmente en pequeñas y medianas empresas. Entre ellas destacan los altos costos económicos, la falta de conocimiento técnico, la escasa asistencia institucional y la ausencia de incentivos fiscales. Estas limitaciones generan desigualdad dentro del sector camaronero y dificultan la transición hacia prácticas sostenibles. El estudio concluye que las certificaciones sí fortalecen la competitividad internacional, pero requieren condiciones previas que aún no están garantizadas para todos los actores. Se recomienda implementar políticas públicas de apoyo, fomentar alianzas empresariales y desarrollar estrategias comerciales que capitalicen los beneficios de la sostenibilidad."
Keywords: SOSTENIBILIDAD; CERTIFICACIÓN; COMPETITIVIDAD; EXPORTACIÓN